Characteristics and prognosis of pediatric myeloid sarcoma in the cytogenetic context of t(8;21). (12th March 2021) - Hu, Guanhua; Lu, Aidong; Wu, Jun; Jia, Yueping; Zuo, Yingxi; Ding, Mingming; Zhang, Leping
Abstract: The prognosis of myeloid sarcoma (MS) is controversial. Many reports indicated that orbital-MS has a good prognosis and is closely related to t(8;21), but the prognostic role of MS in pediatric t(8;21) AML is unclear. We retrospectively analyzed data from 127 patients with pediatric t(8;21) AML diagnosed between January 2010 and June 2018. We compared patients with ( n = 30) and without MS ( n = 97). The median follow-up time was 52.6 months. The proportion of t(8;21) AML patients with MS was 23.6%. Males were more likely to have MS than females. The complete remission rate after the first course of induction chemotherapy and the 3-year relapse-free survival (RFS) among patients with MS were lower than those among patients without MS (60% vs. 78.4%, p = 0.045) (68.8 ± 8.8% vs. 88.0 ± 3.4%, p = 0.004). The female sex and a higher level of RUNX1/RUNX1T1 transcripts after consolidation were risk factors for poor RFS among patients with MS. Our data showed that MS was an independent risk factor in pediatric t(8;21) AML. Close monitoring of measurable residual disease of the bone marrow and extramedullary lesions is needed to guide stratified treatment.